Evaluation the effectiveness of using media content in the educational process of sports specialties students (Sport Science Research, 2024)
This paper examines the effectiveness of utilizing social media and digital platform media content in medical and biological topics for teaching students of sports specialties. The paper separately studies the transformation of teaching methodologies and tools in light of the new digital reality, specifically distance learning. The author conducts a comparative analysis of different types of media, such as videos from social media platforms, comics, infographics, and online labs. The study is conducted using a survey method, involving students from a sports-specific higher education institution. The analysis of results reveals not only a shift in students' perception of information due to the increased use of online resources in traditional instruction, but also a shift in the role of teachers from being the primary source of knowledge to a mentor guiding the learning process.
Keywords: teaching methods, visual perception, media content, distance learning.